A feedback regulation between miR-145 and DNA methyltransferase 3b in prostate cancer cell and their responses to irradiation. Issue 1 (28th May 2015) - Xue, Gang; Ren, Zhenxin; Chen, Yaxiong; Zhu, Jiayun; Du, Yarong; Pan, Dong; Li, Xiaoman; Hu, Burong
Abstract It is believed that epigenetic modification plays roles in cancer initiation and progression. Both microRNA and DNA methyltransferase are epigenetic regulation factors. It was found that miR-145 upregulates while DNMT3b downregulates in PC3 cells. Presence of any negative correlationship and their response to irradiation were investigated in the current study. We found that miR-145 downregulated DNMT3b expression by directly targeting the 3′-UTR of DNMT3b mRNA and knockdown of DNMT3b increased expression of miR-145 via CpG island promoter hypomethylation, suggesting that there is a crucial crosstalk between miR-145 and DNMT3b via a double-negative feedback loop. Responses of the miR-145 and DNMT3b to irradiation are a negative correlation. We also found that either overexpression of miR-145 or knockdown of DNMT3b sensitized prostate cancer cells to X-ray radiation. Our findings enrich the complex relationships between miRNA and DNMTs in carcinogenesis and irradiation stress. It also sheds light on the potential combination of ionizing radiation and epigenetic regulation in prostate cancer therapy.